PRODUCTION OF LOW-CALORIE MANDARIN NECTAR SWEETENED WITH STEVIA AND ITS EFFECT ON QUALITATIVE AND SENSORY PROPERTIES - Basmaa Saaduldeen Sheet; Layla Azhar Ahmed (European Journal of Agricultural and Rural Education, 2022)
A standard sample of mandarin nectar was prepared and sucrose was replaced with Stevia (rebaudioside A) sweetener at 25, 50, 75 and 100%. The physical, chemical and sensory properties of all treated samples were studied while they were stored for 60 days. It was noticed from the results that a significant increase occurred at the end of storage in the values of Total Acid% for sample T4 amounted to 0.689%, Total Soluble Solid% for standard sample T0 amounted to 13,833%, viscosity of sample T0 reached cP 45.600 and the browning index in sample T0 reached 0.425 nm, which means these indicators rose with the progress of the storage period. It was noted from the results that the lowest significant value was at the end of storage for each of the pH of samples T3 and T4, which amounted to 3.367 and 3.366, respectively, and vitamin C in the sample T0 amounted to 39.137 mg/100 ml. The storage period and the treated samples all affected the sensory properties (taste, smell, color and general appearance) of mandarin nectar and the degrees of acceptance of all traits were high at the beginning of storage, but decreased at the end. However, the taste decreased with the increase of the substitution, despite the increase in the color and general appearance in those two samples, due to the bitter taste added by the sweetener.